Tlingit totem poles among the rooftops of Kasaan, Alaska, 1885 - Niblack, Albert P. (Albert Parker), 1859-1929
Totem poles and woodcarvings among the rooftops of Kasaan Alaska, 1885 Caption on mount: Profile view of eastern half of village of Kasa-an, Prince of Wales Island, S. E. Alaska. Photographed by Ensign A.P. Niblack, U.S. Navy. View from roof of house. PH Coll 321.7